New Ways of Managing ConflictLikertRensis and LikertJane Gibson. New Ways of Managing Conflict (New York: McGraw-Hill, 1976), 375 pp., hardback $14.50. - Gibson, James L. (Academy of Management Review, 1976)
This article presents a review of the book ?New Ways of Managing Conflict,? by Rensis Likert and Jane Gibson Likert.